A finite element analysis-computational fluid dynamics coupled analysis on thermal-mechanical fatigue of cylinder head of a turbo-charged diesel engine. (May 2020) - Luo, Xuwei; Zeng, Xiaochun; Zou, Pingping; Lin, Yuxing; Wei, Tao; Yuan, Xiaojun; Liao, Shanbin
A finite element analysis-computational fluid dynamics coupled analysis on the thermo-mechanical fatigue of cylinder head of a turbo-charged diesel engine was performed, and the complete simulation process is illustrated in this paper. In-cylinder combustion analysis and water jacket coolant flow analysis were conducted to provide heat transfer boundary conditions to the temperature field calculation of the cylinder head. Comparing with the conventional finite element analysis of cylinder head by which the heat transfer boundary conditions of the combustion and coolant sides are estimated, the present method coupled the three-dimensional combustion computational fluid dynamics and coolant computational fluid dynamics with the finite element analysis. Both computational fluid dynamics and finite element analysis obtain more accurate boundary conditions on their interface from each other, and thus, the present method improves accuracy of thermo-mechanical fatigue prediction. Based on the measured material performance parameters such as stress–strain curve under different temperatures and E–N curve, creep, and oxidation data material performance, the cylinder head–gasket–cylinder block finite element transient stress–strain field was calculated using ABAQUS. The thermo-mechanical fatigue analysis of cylinder head submodel was performed by using FEMFAT software that is based on the Sehitoglu model to predict the thermo-mechanical fatigue life of cylinder head. By comparing the measured and predicted temperatures of cylinder head, the temperature results showed a good agreement, and the error is less than 10%.